Influence of Thermal and Gustatory Stimulus in the Initiation of the Pharyngeal Swallow and Bolus Location Instroke - Gatto, Ana Rita [UNESP]; Cola, Paula Cristina; da Silva, Roberta Gonçalves [UNESP]; Ribeiro, Priscila Watson [UNESP]; Spadotto, André Augusto [UNESP]; Henry, Maria Aparecida de Arruda Coelho [UNESP] (Elsevier, 2021)
Introduction/Objective: The aim of this study is to analyze the influence of sour taste and cold temperature in the initiation of the pharyngeal swallow (IPS) and bolus location at pharyngeal swallow onset in individuals after stroke. Methods: Cross-sectional prospective study. The study included 52 individuals with unilateral ischemic stroke. Each individual was assessed by videofluoroscopic swallowing study with 5ml of paste bolus offering four different stimuli (natural, cold, sour, and sour-cold). The individuals were divided into two groups according to the offer sequence. Group 1 (G1) – received a randomized sequence of stimuli (24 individuals), and Group 2 (G2) –the stimuli were offered in the following order: natural, cold, sour, and sour-cold(28 individuals). The IPS time and bolus location at pharyngeal swallow onset were analyzed. The bolus location at pharyngeal swallow onset was defined using six different levels. Results: Individuals in G1 did not show a significant difference in IPS time between stimuli. However, individuals in G2 presented a significantly shorter IPS time with the sour and sour-cold stimuli than with natural or cold stimuli. The bolus location at pharyngeal swallow onset did not show significant difference between stimuli in both groups. On the other hand, in the G2 it was observed higher frequency of swallowing with sour-cold stimulus at level 1 (the bolus head was located in any region between the fauces pillar and the point where the tongue crosses the inferior border of the mandible). Conclusion: The sour and sour-cold stimuli influenced the IPS time when they were offered in a sequential order. Moreover, both the IPS time and bolus location at pharyngeal swallow onset were not influenced by the sour and sour cold-bolus when offered in a random sequence.
Keywords: Cold temperature; Deglutition; Deglutition disorders; Sour taste; Stroke